Carbon emissions and economic growth: homogeneous causality in heterogeneous panels - David Maddison; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2008)
This paper introduces the concept of homogeneous non-causality in heterogeneous panels. This concept is used to examine a panel of data for evidence of a causal relationship between GDP and carbon emissions. The technique is compared to the standard test for homogeneous non-causality in homogeneous panels and heterogeneous non-causality in heterogeneous panels. In North America, Asia and Oceania the homogeneous non-causality hypothesis that CO2 emissions does not Granger cause GDP cannot be rejected if heterogeneity is allowed for in the data-generating process. In North America the homogeneous non-causality hypothesis that GDP does not cause CO2 emissions cannot be rejected either.
Keywords: C12; O13; Q54; 330; Energy; carbon emissions; granger causality; heterogeneous panels; Kohlendioxid; Luftverunreinigung; Wirtschaftswachstum; Kausalanalyse; Panel; Schätzung; Welt